PERAN KEPERCAYAAN INTERPERSONAL SEBAGAI MEDIASI KEPEMIMPINAN TRANFORMASIONAL TERHADAP KINERJA PEGAWAI PADA BAPPEDA KABUPATEN WAKATOBI - Asniati Asniati; La Hatani; Wahyuniati Hamid; Samdin Samdin; Nursaban Rommy; La Ode Asfahyadin Aliddin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The purpose of this research is to test and explain the influence of transformational leadership on employee performance through the role of interpersonal trust mediation in BAPPEDA Wakatobi Regency. This research approach is a survey with an explanatory research design. Data collection is done on a online basis using instruments in the form of questionnaires through the https://forms.gle/2wevLGgXLtUmm2Qw6 page. The population of this study is all employees in BAPPEDA Wakatobi Regency as many as 32 people. The analysis equipment used in hypothesis testing is Partial Least Square (PLS). The results showed that transformational leadership has a positive and significant influence on interpersonal trust and employee performance. Interpersonal trust has a positive and significant effect on employee performance. Finally, the results of the study proved interpersonal trust acts as a partial mediation influence between transformational leadership on employee performance. This means that increased interpersonal trust is significantly influenced by transformational leadership. Furthermore, interpersonal trust has a significant contribution to improving employee performance. Finally, good transformational leadership can also contribute significantly toward improvement of employee performance in BAPPEDA Wakatobi Regency